Implementing the Urban Environment Agenda - United Nations Centre for Human Settlements; United Nations Environment Programme (Nairobi, Kenya, 1997)
Why Improve the Urban Environment; How Cities Improve the Urban Environment; How Programmes Support Cities; Sharing Lessons of Experience and Advancing Collective Knowâˆ’How.
Keywords: Environmental -- Planning -- Management; City planning -- Environmental aspects; Urban ecology; Môi trường -- Quy hoạch -- Quản lý; Quy hoạch thành phố; Sinh thái học đô thị